Il ruolo dei pattern agricoli nella creazione di paesaggi rurali identitari - Daniele Torreggiani; Enrica Dall’Ara; Patrizia Tassinari (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
In various historical, geographic and cultural contexts, inhabitants have drawn forms and structures on the landscape fruit of their social, economic and production systems. These signs represent material evidence of a unique geographic and cultural identity. The paper aims at discussing the relationship between uniqueness and universality and related aspects which deal with the mark left by man on the landscape at a large and small scale, thus focusing on base concepts of quality landscape patterns to be adopted in metadesign perspective. The design approach refers to the well-known concept of imageability, which the authors extend to the countryside where it has the potential of being fertile ground for new planning and design of rural settlements.